2018
DOI: 10.26442/terarkh201890648-54
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-23 (FGF-23) / soluble Klotho protein (sKlotho) / sclerostin glycoprotein ratio disturbance is a novel risk factor for cardiovascular complications in ESRD patients receiving treatment with regular hemodialysis or hemodiafiltration

Abstract: Aim of the study was to explore the role of the FGF-23/sKlotho/sclerostin ratio disturbance in the determining of cardiovascular risk in end stage renal disease (ESRD) patients, receiving treatment with regular hemodialysis (НD) or hemodiafiltration (НDF) online in Russia. Materials and methods. 42 patients with ESRD, at the age of 18-55 years, treated with HD or HDF on line for at least 6 months, were examined. 22 (52.3%) patients received traditional HD, the remaining 20 (47.7%) - HDF online. In all the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…CIMT and AAC grade were used in this study to judge the development of cardiovascular thickening and calcification. The results observed the rising of both CIMT and AAC grades in patients with a lower level of klotho, which were like previous studies (13,15,(23)(24)(25). The mechanism of how decreased serum soluble klotho level leads to cardiovascular thickening and calcification is not clear to date.…”
Section: Discussionsupporting
confidence: 85%
“…CIMT and AAC grade were used in this study to judge the development of cardiovascular thickening and calcification. The results observed the rising of both CIMT and AAC grades in patients with a lower level of klotho, which were like previous studies (13,15,(23)(24)(25). The mechanism of how decreased serum soluble klotho level leads to cardiovascular thickening and calcification is not clear to date.…”
Section: Discussionsupporting
confidence: 85%
“…A number of researches demonstrated that FGF23 can regulate a variety of signaling pathways in human body, such as mineral metabolism, insulin resistance, energy balance, premature aging, etc. (Lacroix & Urena-Torres, 2020;Milovanova et al, 2018). Combination of Klotho with fibroblast growth factor receptor 1 (FGFR1) can form a transmembrane co-receptor of FGF23 to regulate FGF23/FGFR1/Klotho signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, other authors showed that increased levels of ox-LDL induce a decrease in renal expression of klotho [235]. A recent study conducted in patients treated by HD showed that higher serum FGF-23 levels and lower levels of sKL and sclerostin (endogenous Wnt inhibitor) were associated with chronic inflammation, malnutrition, and secondary hyperparathyroidism, and they may be considered as prognostic factors for CVD and its complications, such as left ventricular hypertrophy, acute coronary syndrome, or cardiac arrhythmias [236]. On the other hand, data on the relationship between klotho and kidney function are divergent.…”
Section: Klotho Proteinmentioning
confidence: 99%